The efficacy of Olfen-plaster drug preparation in treating pains in the lower back of old patients - Povorozniuk, Vladyslav; Bystritskaya, M.; Karasevskaya, T.; Orlik, Tatyana (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The back pain is the most popular dieses of the osseous-muscle system. The substantial part of the reasons of the back pain make degenerative dystrophic spine diseases. The leading position among existent medicine arsenal in back pain treatment are occupied by non-steroid anti-inflammatory drugs, however using medicine of this group very often leads to the different complications on the part of the gastrointestinal tract, especially when this medicines are taken by the advanced age people. One of the alternative how to solve this problem is using of the local medicine without systemic action. In the article are presented the research results in study of the effectiveness, safety and tolerance of the „Olfen ™-140 мg transdermal plaster” medicine, in complex of the back pain treatment at advance age group patients in comparison with the effectiveness of the diclofenac sodium. It is fixed the authentic reduction of the intensity of the verbal pain syndrome, improving of the life activity and increasing of the motility regime (р<0,05). Is was not found authentic difference in the dynamic of the index between groups. At the patients of the researched group there were found no side effects, connecting with taking of the medicines.